2004
DOI: 10.1081/jdi-200031759
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐N‐Like and Anti‐Form Red Cell Antibodies in Chronic Hemodialysis Patients

Abstract: Allogeneic red blood cell (RBC) transfusions and the use of reusable dialyzers sterilized with formaldehyde can lead to RBC alloimmunization in chronic hemodialysis patients. The formed RBC alloantibodies have been implicated in immediate kidney allograft failure and decreased RBC survival observed in these patients. Using indirect antiglobulin test, direct antiglobulin test (DAT), and direct Polibrene test (DPT), we detected an RBC alloimmunization rate of 17.2% (11/64) in transfused hemodialysis patients, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…These agents lead to hemolysis by establishing oxidant damage in erythrocytes (Kjellstrand et al, 1974;Carlson&Shapiro 1970;Calderaro & Heller 2001;Blomfield et al, 1969). Reducing injury generally arises because of the formaldehyde used in the dialyzer sterilization process (Fonseca et al, 2004). Osmolar injury generally develops secondary to hypotonic dialysate use (Said et al, 1977).…”
Section: Hematological Complicationsmentioning
confidence: 99%
“…These agents lead to hemolysis by establishing oxidant damage in erythrocytes (Kjellstrand et al, 1974;Carlson&Shapiro 1970;Calderaro & Heller 2001;Blomfield et al, 1969). Reducing injury generally arises because of the formaldehyde used in the dialyzer sterilization process (Fonseca et al, 2004). Osmolar injury generally develops secondary to hypotonic dialysate use (Said et al, 1977).…”
Section: Hematological Complicationsmentioning
confidence: 99%
“…However the specificity of DAT was more. They concluded that formaldehyde specific antibodies could increase the risk of hemolysis, reduce the survival of red cells and increase the need for blood transfusions in these patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…38 A number of historical studies have shown the link between formaldehyde-sterilized dialyser and formation of RBC alloantibodies, particularly anti-N like and anti-Form antibodies. [38][39][40][41][42] It is postulated that formaldehyde exposure to RBC NM receptor (terminal N-acetylneuraminic acid group of M substance) can trigger an immunogenic response. 41 In 1976, an outbreak of haemolytic anaemia was linked to formaldehyde contamination following installation of a new filter system.…”
Section: Chemical Contamination: Sterilizing Agentsmentioning
confidence: 99%
“…It alters the redox state of the erythrocyte, leading to inhibition of glycosis and decline in adenosine triphosphate (ATP) stores that can promote haemolysis . A number of historical studies have shown the link between formaldehyde‐sterilized dialyser and formation of RBC alloantibodies, particularly anti‐N like and anti‐Form antibodies . It is postulated that formaldehyde exposure to RBC NM receptor (terminal N‐acetylneuraminic acid group of M substance) can trigger an immunogenic response .…”
Section: Causesmentioning
confidence: 99%